Nuclear Energy From Current Perspective: A Short Review - Siti Amira Othman, (Enhanced Knowledge in Sciences and Technology, 2023)
It is important for a country’s growth and wellbeing to have access to reliable and secure energy supplies at decent cost. Nonetheless, some people fail to recognize the importance of energy and take it for granted because they are unaware of the impact of energy source on their daily life. As the globe battles to restrict carbon dioxide and green gas emission, as well as deal with climate change, nuclear energy begins to catch everyone’s attention. Climate change and diminishing fossil fuel supply have sparked a nuclear renaissance. This paper discusses about how the nuclear energy bring benefits to the industry and country development.